0023 Screen Time and Insomnia Symptoms in University Students. (25th May 2022) - Hodges, Nicholas; Zhou, Eric; Trevorrow, Tracy; Dietch, Jessica
Abstract: Introduction: Prior research has demonstrated a relationship between screen time and sleep health, but more work is needed to understand the potential impact of reason for screen time and timing (i.e., weekend vs. weekday). This study aimed to determine whether screen time, and reason for use, was associated with insomnia symptoms in a sample of university students during the school term. Further, we sought to determine whether effects differed by weekend/weekday. Methods: Participants were 767 enrolled students from two universities (age x̄=20.94 [SD=5.25]; 74% women). Insomnia symptoms were assessed with the Insomnia Severity Index (ISI); screen time was a self-report of average daily screen time for a variety of purposes (productivity, social media, streaming media, browsing the internet, or video games) on weekdays/workdays and weekends/off days. Results: A total of 16.4% of the sample had insomnia symptoms in the clinical range (ISI x̄=9.1 [SD=5.3]). Participants reported 10.0 hours (SD=4.5) of screen time per day on weekdays and 10.8 hours (SD=5.2) per day on weekends. During the week, the most screen time (44%; x̄=4.4 [SD=2.6] hours/day) was spent on productivity (work or school). On weekends, the most screen time (30%; x̄=3.3 [SD=2.1] hours/day) was spent on streaming media. More screen time on the weekends was associated with greater insomnia symptoms (r=.10, p=.004), but not during the week (r=.05, p=.185). Regression analyses indicated weekend screen time accounted for 2% of the variance in insomnia symptoms, and this relationship was driven by screen time for productivity (beta=.09, p=.017) and video games (beta=.09, p=.019). Conclusion: Among university students, self-reported screen time during the week was not associated with elevated insomnia symptoms. Weekend screen time, particularly for the purpose of productivity and video games, was associated with elevated insomnia symptoms though the effect was small. Although screen time is often highlighted as a key contributor to poor sleep health, this impact was minimal in the current study. Future work should continue to examine whether different motivations for screen time is associated with various facets of sleep health, and delineate these associations by weekend vs. weekday. Support (If Any): None